Fate and Occurrence of Pharmaceutically Active Organic Compounds during Typical Pharmaceutical Wastewater Treatment - Qiao Luo; Jing Wang; JianHui Wang; Yu Shen; Peng Yan; YouPeng Chen; ChengCheng Zhang (Journal of Chemistry)
The chemical composition, distribution, and fate of pharmaceutically active compounds (PhACs) present in typical pharmaceutical wastewater treatment plants were investigated with the aim of effectively removing these pollutants while minimizing waste of resources and energy. The results of this study indicate that the relative content of an organic compound class is unrelated to the number of organic compounds in the influent and effluent, yet it is directly proportional to the pollution contribution in pharmaceutical wastewater. In wastewater influent, the organic compound classes with the highest relative contents and pollution contributions were acids (relative content = 63.65%, contribution to pollution = 67.22%), esters (44.96%, 41.24%), and heterocyclic compounds (30.24%, 35.23%); in wastewater effluent, these classes were organic acids (62.54%, 65.13%), esters (52.66%, 59.02%), and organosilicon compounds (42.46%, 37.45%). The different physicochemical characteristics of these pollutants result in different removal efficiencies. For example, N,N-dimethylformamide, 4-methyloctane, N-ethylmorpholine, and 4-amino-N,N- and N,N-diethylbenzamide are refractory and are not degraded by microorganisms; thus, these compounds are discharged into the aquatic environment. Other organic compound classes including organosilicon compounds, acids, esters, heterocycles, and alcohols are mostly biodegraded, which leads to high concentrations of hydrocarbons in the wastewater effluent. The results of this study provide a foundation for the improvement of pharmaceutical wastewater treatment.